Evaluation of risk of malignancy index in adnexal masses at a tertiary hospital: a prospective study - Behera, Ritanjali; Pradhan, Paramita; Misra, Bharati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The discrimination between benign and malignant adnexal masses is important in deciding clinical management and optimal surgical planning. The aim of the study was to evaluate the effectiveness of risk of malignancy index (RMI) to identify cases with high potential of ovarian malignancy at a tertiary hospital. Methods: This prospective study was conducted over a period of two years from September 2017 to August 2019 at obstetrics and gynecology department of M. K. C. G. Medical College and Hospital, Berhampur. A total case of 130 patients with adnexal masses who underwent surgical treatment were included as histopathological report was taken as gold standard to calculate accuracy of RMI. Results: Of the total masses, 85 (65.4%) were benign and 45 (34.6%) were malignant. The mean age of patients was 41.03±14 years. The best cut off value for the RMI-3 was 225 with highest area under the ROC curve 87%, sensitivity of 75.55%, specificity of 98.82%, PPV of 97.14%, NPV of 88.42% and an accuracy of 90.76%. Conclusions: The present study demonstrated that RMI was a reliable method in detecting malignant ovarian tumors. The RMI is a simple and practically applicable tool in preoperative discrimination between benign and malignant adnexal masses in non-specialized gynecologic departments, particularly in developing countries.